Toxic Epidermal Necrolysis-Like Reaction Following Combination Therapy With Camrelizumab and Apatinib for Advanced Gallbladder Carcinoma - Yang, Yonghao; Li, Jun; Till, Brian G.; Wang, Jun; Zhang, Bicheng; Wang, Hanping; Huang, Hao; Li, Tiepeng; Gao, Quanli; Li, Hongle; Wang, Zibing (Frontiers in Oncology, 2021)
Recently, combination regimens based on programmed cell death-1 (PD-1) blockade have become increasingly common in clinical practice for the treatment of cancer. Such combinations significantly improve efficacy, but treatment-related adverse events have also become more complex and severe. Here, we report an acute toxic epidermal necrolysis (TEN)-like reaction in a patient with gallbladder cancer who received camrelizumab (an anti-PD-1 antibody) in combination with apatinib. Interestingly, distinct clinical and pathological characteristics were observed that differed from those of the reported cases of severe cutaneous reactions induced by anti-PD-1 antibodies alone; thus, we speculate that it was induced by the combination of camrelizumab and apatinib. It is worth noting that the TEN-like reaction showed resistance to methylprednisolone initially, which was gradually resolved after the addition of intravenous immunoglobulin (IVIg). Immunohistochemical staining revealed that the skin lesion was infiltrated by moderate numbers of CD4+ T cells and large numbers of CD8+ T cells during the progression of the TEN-like reaction, and mass cytometry by time-of-flight showed a significant reduction in the CD4+ and CD8+ T cell proportions in the peripheral blood after the rash improved. All these findings highlight the essential role of CD4+ T cells and CD8+ T cells in the TEN-like reaction induced by camrelizumab plus apatinib treatment, and we speculate that T cells, especially CD8+ T cells, attack keratinocytes. In conclusion, the TEN-like reaction induced by camrelizumab and apatinib deserves clinical attention, and further work is needed to elucidate the exact pathophysiologic mechanism as well as the optimal management strategy.